Genotype Analysis of Clinical Candida albicans Isolates Using PCRs Targeting 25S rDNA and ALT Repeat Sequences of the RPS and Antifungal Susceptibility in Ouagadougou (Burkina Faso) - Sawadogo PM; Zida A; Soulama I; Sermé SS; Guiguemdé KT; Junior R; Sangaré I; Bamba S; Ouédraogo-Traoré R; Guiguemdé TR (Infection and Drug Resistance, 2019)
Patindoilba Marcel Sawadogo,1–3 Adama Zida,1–3 Issiaka Soulama,3,4 S Samuel Sermé,4 Kiswendsida Thierry Guiguemdé,2,5 Richard Junior,1 Ibrahim Sangaré,5,6 Sanata Bamba,5,6 Rasmata Ouédraogo-Traoré,2,7 Tinga Robert Guiguemdé6,8 1Parasitology-Mycology Department, University Hospital Yalgado Ouédraogo, Ouagadougou, Burkina Faso; 2Training and Research Unit in Health Sciences, University Joseph Ki-Zerbo (UO JKZ), Ouagadougou, Burkina Faso; 3Private School of Health News Sciences (ESSN), Ouagadougou, Burkina Faso; 4National Center for Research and Training on Malaria, Ouagadougou, Burkina Faso; 5Parasitology-Mycology Department, Souro Sanou University Hospital, Bobo Dioulasso, Burkina Faso; 6High Institute of Health Sciences, University Nazi Boni, Bobo Dioulasso, Burkina Faso; 7Laboratory Department, University Hospital Charles De Gaulles, Ouagadougou, Burkina Faso; 8Muraz Research Center, Bobo-Dioulasso, Burkina FasoCorrespondence: Patindoilba Marcel SawadogoParasitology-Mycology Department, University Hospital Yalgado Ouédraogo, 03 BP 7022 Ouaga 03, Ouagadougou, Burkina FasoTel +22672112786Email sawadogopmarcel@yahoo.frObjective: Candida albicans is a yeast with multiple genotypes. It’s a commensal fungus colonizing various sites. However, when the host’s immune system weakens, it becomes pathogenic and is responsible for various lesions. In Burkina Faso, antifungal drugs are frequently used, particularly fluconazole, the most used systemic antifungal. This antifungal drug and other antifungal drugs are often used for self-medication or prescribed outside of antifungal susceptibility test results. These situations led to the emergence of Candida albicans strains resistant to antifungal drugs commonly used in Burkina Faso. The aim of this study was to determine the types of Candida albicans using PCRs targeting 25S rDNA and ALT repeat sequences of the RPS and to establish their azoles and polyenes susceptibility profile.Material and methods: Antifungal susceptibility testing by disk diffusion method was performed in accordance with CLSI document M44-A for yeasts and the manufacturer’s instructions. Candida albicans isolates were genotyped using specific PCR primers of the rDNA and RPS genes.Results: Ten (10) RPS types of Candida albicans were found in our study: The most common RPS types are A3 (40.6%), A2 (24.0%) and A2/3 (14.6%) for genotype A, B2/3 (5.2%) for genotype B and C2 (3.2%) for genotype C. The Azole resistance, especially fluconazole (74.4%), was the most common with genotype A, including A3 (36.6%), A2 (18. 3%). Polyene resistance was rare with nystatin, only A3 (1.2%) resistant isolate to nystatin was observed. For amphotericin B, the highest observed resistance rates were A3 (11.0%) and A2/3 (8.5%) for the genotype A and B2 (10.0%), B3 (10.0%) and B2/3 (10.0%) for genotype B.Conclusion: Our study showed that Candida albicans resistance to azoles, especially to fluconazole, is an important phenomenon in Ouagadougou, and several genotypes RPS types are involved. Thus, fluconazole would not be an antifungal agent for first-line prescribing for treatment of candidiasis in Ouagadougou. This study will be continued to determine the molecular mechanisms involved in these antifungal resistances, for further research of new molecules with different action targets.Keywords: Candida, rDNA, RPS, antifungal, susceptibility, Burkina Faso